LINGUISTIK FUNGSIONAL : DIMENSI DALAM BAHASA - Bahagia Saragih (BAHAS, 2016)
This article deals with the explanation about a small part of the study of Systemic Functional Linguistics (SFG), i.e. dimension in language. Systemic Functional (SF) theory views language as a social semiotic a resource people use to accomplish their purposes by expressing meanings in context. Language is a systematic resource for expressing meaning in context and linguistics, the study of how people exchange meanings through the use of language. This view of language as a system for meaning potential implies that language is not a well defined system not a